2023
DOI: 10.1038/s41467-023-36321-6
|View full text |Cite
|
Sign up to set email alerts
|

T cell-independent eradication of experimental glioma by intravenous TLR7/8-agonist-loaded nanoparticles

Abstract: Glioblastoma, the most common and aggressive primary brain tumor type, is considered an immunologically “cold” tumor with sparse infiltration by adaptive immune cells. Immunosuppressive tumor-associated myeloid cells are drivers of tumor progression. Therefore, targeting and reprogramming intratumoral myeloid cells is an appealing therapeutic strategy. Here, we investigate a β-cyclodextrin nanoparticle (CDNP) formulation encapsulating the Toll-like receptor 7 and 8 (TLR7/8) agonist R848 (CDNP-R848) to reprogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 47 publications
3
21
0
Order By: Relevance
“…In addition to the direct effects of GO:R848 on macrophages and microglia, we also observed that this immunomodulatory nanocomplex was able to alter the wider GBM microenvironment and inhibit tumour progression. Our data further corroborate recent findings that intratumoral activation of TLR7/8 can alter the tumour microenvironment, increase peripheral lymphocyte infiltration into the tumour and inhibit tumour growth 24,[57][58][59] . The immunosuppressive microenvironment and paucity of tumour reactive lymphocytes has been identified as a limiting factor to the efficacy of immunotherapies.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to the direct effects of GO:R848 on macrophages and microglia, we also observed that this immunomodulatory nanocomplex was able to alter the wider GBM microenvironment and inhibit tumour progression. Our data further corroborate recent findings that intratumoral activation of TLR7/8 can alter the tumour microenvironment, increase peripheral lymphocyte infiltration into the tumour and inhibit tumour growth 24,[57][58][59] . The immunosuppressive microenvironment and paucity of tumour reactive lymphocytes has been identified as a limiting factor to the efficacy of immunotherapies.…”
Section: Discussionsupporting
confidence: 91%
“…From a host−guest chemistry point of view, we observed a two-phase drug release behavior which was expected for a drug delivery system that utilizes macromolecular host−guest interactions such as small-molecule payload (guest) complexing to cyclodextrins (host). 13,48 The two-phase release can be often desirable to provide an initial rapid therapeutic effect followed by a slower sustained and prolonged release. 49 The initial rapid-release phase could be mainly attributed to weaker host−guest interactions occurring on the particles surface.…”
Section: Acs Nanomentioning
confidence: 99%
“…Most prior research has used nanoformulations to deliver small-molecule toll-like receptor (TLR) and cGAS/stimulator of interferon genes (STING) pathway agonists to TAM. Some of these nanoformulations have shown antitumor efficacy in mouse models of cancer, while others have limited efficacy , and/or exhibit unacceptable systemic toxicity . The diverging efficacy data are not entirely unexpected and are evidence that we still do not fully understand TAM function and reprogrammability.…”
mentioning
confidence: 99%
“…3 Promoting an inflammatory (M1-like) phenotype in tumor-associated macrophages is therefore one approach to inhibit cancer progression. 4,5 In contrast, M1-like macrophages initially dominate the immune landscape in injured tissue and participate in the clearance of apoptotic cells and early tissue remodeling. 6 A subsequent transition toward populations dominated by an M2-like phenotype is required for tissue healing, 7 including by mitigation of inflammatory cytokine production and concurrent growth factor production that is lacking in many contexts and leads to progressive disease (e.g., the development of ischemic heart failure and chronic kidney disease).…”
Section: Introductionmentioning
confidence: 99%
“…It is understood, however, that tumor-associated macrophages typically present an anti-inflammatory or reparatory (M2-like) phenotype that promotes tumor growth, undermines immunotherapeutic response, and correlates with poor patient prognosis . Promoting an inflammatory (M1-like) phenotype in tumor-associated macrophages is therefore one approach to inhibit cancer progression. , In contrast, M1-like macrophages initially dominate the immune landscape in injured tissue and participate in the clearance of apoptotic cells and early tissue remodeling . A subsequent transition toward populations dominated by an M2-like phenotype is required for tissue healing, including by mitigation of inflammatory cytokine production and concurrent growth factor production that is lacking in many contexts and leads to progressive disease (e.g., the development of ischemic heart failure and chronic kidney disease). , The inhibition of inflammatory signaling and modulation of macrophage phenotype has therefore emerged as a critical therapeutic target in tissue healing. , …”
Section: Introductionmentioning
confidence: 99%